Ultrasound-assisted lipase catalyzed hydrolysis of aspirin methyl ester - Chiplunkar, Pranali P. (2018)
Supplementary data associated with this article can be found, in the online version, at http://dx.doi.org/10.1016/j.ultsonch.2017.08.004.